A microfluidic platform to study the effects of vascular architecture and oxygen gradients on sickle blood flow. (July 2017) - Lu, Xinran; Galarneau, Michelle M.; Higgins, John M.; Wood, David K.
Abstract: Our goal was to develop a model of the microvasculature that would allow us to quantify changes in the rheology of sickle blood as it traverses the varying vessel sizes and oxygen tensions in the microcirculation. We designed and implemented a microfluidic model of the microcirculation that comprises a branching microvascular network and physiologic oxygen gradients. We used computational modeling to determine the parameters necessary to generate stable, linear gradients in our devices. Sickle blood from six unique patients was perfused through the microvascular network and subjected to varying oxygen gradients while we observed and quantified blood flow. We found that all sickle blood samples fully occluded the microvascular network when deoxygenated, and we observed that sickle blood could cause vaso‐occlusions under physiologic oxygen gradients during the microvascular transit time. The number of occlusions observed under five unique oxygen gradients varied among the patient samples, but we generally observed that the number of occlusions decreased with increasing inlet oxygen tension. The model system we have developed is a valuable tool to address fundamental questions about where in the circulation sickle‐cell vaso‐occlusions are most likely to occur and to test new therapies.